Analysis of the Turkish pre-service teachers views on pedagogical independence in terms of various variables - Akpinar, Burhan (Sila Science, 2012)
Pedagogical independence is one of the absolute musts for the full independence of a country. The subject of pedagogical independence is being discussed in Turkey which has some important experiences in this regard. In these discussions, the views of pre-service teachers, who are of those that will direct the pedagogy of Turkey in the future, are very significant. This study, which aims to determine the pre-service teachers' views on pedagogical independence, is of a descriptive character. The data of the study have been obtained with a questionnaire from 1210 pre-service teachers still receiving education at various universities in Turkey. As a result of the analysis of the data, the following have been identified: The Turkish pre-service teachers think that the Turkish Educational System (TES) is not independent, and that it is under the influence of the USA and EU, thus they feel uncomfortable about this situation. And they think that the reasons for this are Westernization, inadequacies in science-culture-art, and globalization. These pre-service teachers, who find pedagogical independence necessary for the full independence, are of the opinion that an independent TES compatible with our own history and culture, and for this, they have expectations from teachers and the Ministry of National Education (MNE).
Keywords: Pedagogical independence; Pre-service teachers' views; Turkish educational system